P53 versus inflammation: an update. Issue 2 (17th January 2020) - Kubra, Khadeja-Tul; Akhter, Mohammad S.; Uddin, Mohammad A.; Barabutis, Nektarios
ABSTRACT: Etiologies of human pathophysiology have been associated with states of severe inflammation. The endothelium defender P53 supports cellular functions, by orchestrating anti-inflammatory responses. The purpose of the present article is to provide an update on the mechanisms enforcing the protective actions of P53 in human homeostasis, and to discuss current efforts on the development of new therapies against inflammatory abnormalities.